WANITA, DISIPLIN DAN KUASA TUBUH: KEPATUHAN TUBUH MELALUI DIET DALAM PERSPEKTIF FOUCAULDIAN - Evi Lailatul Jannah; Medhy Aginta Hidayat (Jurnal Analisa Sosiologi, 2024)
This research examines the discipline and power of the body that occurs in the bodies of women on diets. Women are often objectified in society because of their behaviors, obligations, social values, and even their bodies. As a result of this objectification, an idealized image of the female body emerges in society. This construction causes women to be dissatisfied with their bodies both biologically and aesthetically, which makes them feel inferior and compare themselves to the ideal body image. Women's desire to fulfill this image leads them to self-control, which can be achieved through dieting. Some popular diet methods are calorie deficit and intermittent fasting (IF), which are also practiced by many women who are followers of the X (Twitter) account @diethingy. This research uses the theory of discipline and power of the body introduced by Michel Foucault using qualitative research methods and a phenomenological study approach. The data collection techniques used were observation and interviews conducted online. This research uses a purposive sampling technique to determine informants—data checking and validity techniques using source triangulation. The results of this study show that not all women go through a complete disciplinary process, as Foucault conveys. Most of the women in this study feel they have power over themselves. However, in reality, this power is pseudo-power because the women are not completely free and are still bound by power relations in society.